Bite Force and Influential Factors on Bite Force Measurements: A Literature Review - Koc, Duygu; Dogan, Arife; Bek, Bulent (European Journal of Dentistry, 2010)
Maximum voluntary bite force is an indicator of the functional state of the masticatory system and the level of maximum bite force results from the combined action of the jaw elevator muscles modified by jaw biomechanics and reflex mechanisms. The measurement of bite force can provide useful data for the evaluation of jaw muscle function and activity. It is also an adjunctive value in assessing the performance of dentures. Technological advances in signal detection and processing have improved the quality of the information extracted from bite force measurements. However, these measurements are difficult and the reliability of the result depends on a number of factors, such as presence of pain and temporomandibular disorders, gender, age, cranio-facial morphology, and occlusal factors. In addition to these physiological factors, recording devices and techniques are important factors in bite force measurement. Therefore, one should be careful when comparing the bite force values reported in the research. (Eur J Dent 2010;4:223-232)
Keywords: Bite force; Bite force recording devices; Temporomandibular disorders